1993
DOI: 10.1159/000187478
|View full text |Cite
|
Sign up to set email alerts
|

<sup>31</sup>P Magnetic Resonance Spectroscopy Investigation of Skeletal Muscle Metabolism in Uraemic Patients

Abstract: Using the method of in vivo magnetic resonance spectroscopy we examined 17 patients with moderately advanced chronic renal insufficiency, 21 patients with chronic renal failure treated by haemodialysis, and 15 dialyzed patients with symptomatic renal osteopathy. The ratios of intracellular phosphocreatine and inorganic phosphate concentrations of these subjects measured at rest were compared with those found in healthy controls. While we noted significantly lower (p < 0.01) ratio values in all patients, subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…Of the remaining case-control studies, seven 15,[36][37][38][39][40][41] included participants with chronic renal disease not on HD and with comorbidities (clinical evidence of polyneuropathy, varying degrees of paresis, myopathy, renal bone disease, cerebrovascular accident, diabetes mellitus, peripheral vascular disease, etc. ); four included male participants only; [42][43][44][45] and five [46][47][48][49][50] did not provide adequate description of the participants included in the study. Inclusion of participants with clinical evidence of neuromuscular involvement, wide age ranges, and comorbidities that could contribute to neuromuscular impairment suggested possible selection bias that could confound the outcomes of these studies.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Of the remaining case-control studies, seven 15,[36][37][38][39][40][41] included participants with chronic renal disease not on HD and with comorbidities (clinical evidence of polyneuropathy, varying degrees of paresis, myopathy, renal bone disease, cerebrovascular accident, diabetes mellitus, peripheral vascular disease, etc. ); four included male participants only; [42][43][44][45] and five [46][47][48][49][50] did not provide adequate description of the participants included in the study. Inclusion of participants with clinical evidence of neuromuscular involvement, wide age ranges, and comorbidities that could contribute to neuromuscular impairment suggested possible selection bias that could confound the outcomes of these studies.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Higher levels of PCr and ATP concentration were noted by three studies. 40,41,50 According to Nishida et al, 44 however, muscle weakness may be associated with lower concentrations of resting PCr and ATP values in people with ESRD/HD, since these lowered concentrations are consistent with reduced energy production at rest. Nishida et al's 44 suggestion is supported by findings of lowered resting PCr and ATP in one other casecontrol study.…”
Section: Energy Metabolism: In Vivo Studiesmentioning
confidence: 98%
“…Since evidence of normal mitochondrial oxidative capacity in CRF patients has been reported (11,18), and the companion study showed that O 2 peak is O 2 supply dependent in these rHuEPO treated patients, changes in muscle bioenergetics at maximum exercise after rHuEPO therapy must follow those of maximal O 2 flow from muscle capillary to mitochondria. However, different reports examining muscle cell bioenergetics in these patients provide conflicting results (18)(19)(20)(21)(22). The primary aim of the present study was the analysis of the relationships between muscle O 2 transport and cellular bioenergetics, assessed by 31 P-nuclear magnetic resonance spectroscopy ( 31 P-MRS), before and after erythropoietin therapy.…”
mentioning
confidence: 97%
“…However, little studies have examined cardiovascular responses to the muscle metaboreflex in patients with CRF in initial stage. Patients with CRF have severe myopathy (Diesel et al ., ; Kouidi et al ., ; Sakkas et al ., ) coupled with a reduction in muscle blood flow (BF) and metabolic abnormalities during exercise (Moore et al ., ; Taborsky et al ., ). In this study, we tested the hypothesis that patients with CFR initial with myopathy may evoke a significant reduction of muscle BF and metabolic abnormalities during handgrip exercise, attenuating skeletal muscle metaboreflex.…”
Section: Introductionmentioning
confidence: 97%
“…However, little studies have examined cardiovascular responses to the muscle metaboreflex in patients with CRF in initial stage. Patients with CRF have severe myopathy (Diesel et al, 1990;Kouidi et al, 1998;Sakkas et al, 2004) coupled with a reduction in muscle blood flow (BF) and metabolic abnormalities during exercise (Moore et al, 1993;Taborsky et al, 1993).…”
Section: Introductionmentioning
confidence: 99%